INDEX ANALYSIS IN MEASURING THE FINANCIAL PERFORMANCE OF BSI AS A BULLION BANK - Saputra, Bayu Akbar; Faizah, Iva (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
The development of Islamic banking in Indonesia is increasingly dynamic, especially with the presence of Bank Syariah Indonesia (BSI) as a Bullion Bank after the issuance of PJOK No. 17 of 2024 concerning the Implementation of Bullion Business Activities. The issue that arises is how the implementation of bullion business affects BSI's financial performance, especially in terms of profitability. This study aims to analyze BSI's financial performance before and after operating as a Bullion Bank using index analysis. The research method used is a quantitative approach with a descriptive comparative method, using secondary data in the form of BSI's monthly financial reports for 2024 and 2025 as well as a review of related literature. The results show that although the Gross Profit Margin (GPM) and Net Profit Margin (NPM) ratios tended to decline in percentage terms, both remained above the industry average (30% for GPM and 20% for NPM), so that BSI was still categorized as healthy. In nominal terms, gross profit, net profit, and revenue actually increased, especially after the implementation of the bullion business regulation. In conclusion, the implementation of the bullion business has contributed positively to the increase in BSI's profitability and stability, even though there is a downward trend in profitability ratios.